Preschool children in Danish out-of-hours primary care: a one-year descriptive study of face-to-face consultations - Jørgen Lous; Grete Moth; Linda Huibers; Peter Vedsted; Morten Bondo Christensen (BMC Family Practice, 2019)
Abstract Background The demand for out-of-hours (OOH) primary care has increased during the last decades, with a considerable amount of contacts for young children. This study aims to describe the reasons for encounter (RFE), the most common diagnoses, the provided care, and the parental satisfaction with the general practitioner (GP) led OOH service in a Danish population of children (0–5 years). Methods We conducted a one-year cross-sectional study based on data for 2363 randomly selected contacts concerning children from a survey on OOH primary care including 21,457 patients in Denmark. For each contact, the GPs completed an electronic pop-up questionnaire in the patient’s medical record. Questionnaire items focussed on RFE, health problem severity, diagnosis, provided care, and satisfaction. The parents subsequently received a postal questionnaire. Results The most common RFE was non-specific complaints (40%), followed by respiratory tract symptoms (23%), skin symptoms (9%), and digestive organ symptoms (8%). The most common diagnosis group was respiratory tract diseases (41%), followed by general complaints (19%) and ear diseases (16%). Prescriptions were dispensed for 27% of contacts, and about ¾ were for antibiotics. A total of 12% contacts concerned acute otitis media; antibiotics were prescribed in 70%. A total of 38% of contacts concerned fever, and ¼ got antibiotics. A total of 7.4% were referred for further evaluation. The parental satisfaction was generally high, but 7.0% were dissatisfied. Dissatisfaction was correlated with low prescription rate. Conclusion Respiratory tract diseases were the most common diagnoses. The GPs at the OOH primary care service referred children to hospital in 7.4% of the face-to-face consultations, and the provided care was evaluated as non-satisfying by only 7.0% of the parents. Clinical implications of the findings mean room for less prescription of antibiotic to children with ear diseases and a need for research in factors related to dissatisfaction.